How about nano? Impact of size of plastics on plastic pollution and the magnitude of the problem - Sarper Sarp (Universitas Pakuan, 2023)
In the last decade we have realized that the plastics we use every day, and for practically everything, may be the biggest environmental polluters humans have ever released to the environment (EU DG, 2011). Since the first reports of plastic pollutions, we have learned so much about the issue. Macro and micro plastic pollution topics have been extensively studied, investigated, regulated, and in some cases litigated (Uren Webster et al., 2020)(Barnes, Galgani, Thompson, Barlaz, 2009)(Environment Agency, 2018). As it happened in most of the past cases, we have started with the most obvious and visible problem: macro plastics.